Composite structure, terminal shell, composite structure preparation method and shell preparation method

By forming an intermediate layer of a specific structure between the titanium alloy and the lightweight metal material, the problem of low shear strength in the composite structure in the prior art is solved, and the overall strength and thermal stability are improved.

CN115874178BActive Publication Date: 2025-01-03HUAWEI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111155037.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-29
Publication Date
2025-01-03
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

In the prior art, after titanium alloy and light metal materials (such as aluminum alloy or magnesium alloy) are combined by stacking welding, the interface shear strength is lower, and the interface shear strength drops sharply after heat treatment, resulting in thermal stability of the composite structure. Poor sex.

Method used

By forming an intermediate layer between the titanium alloy and the light metal material, the intermediate layer includes a first transition layer, a stabilizing layer and a second transition layer, the mass fraction change rate of the light metal element is controlled, the interface shear strength is improved, and through Solid-liquid diffusion forms a high-strength composite structure.

Benefits of technology

It significantly improves the overall strength and interface shear strength of the composite structure, extends the formation time of the intermediate layer, and enhances the application scenarios of the composite structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115874178B_ABST
    Figure CN115874178B_ABST
Patent Text Reader

Abstract

A composite structure includes a titanium alloy, a light metal material, and an intermediate layer. The intermediate layer is formed between the titanium alloy and the light metal material. The intermediate layer includes a first transition layer, a stabilization layer, and a second transition layer. The average change rate of the mass fraction of the light metal element in the first transition layer is |K L‑1 |>30% / μm. Average change rate of the mass fraction of light metal elements in the second transition layer |K L‑2 |>45% / μm. Average change rate of high mass fraction of light metal elements in the stable layer |K L‑w |<15% / μm. The light metal material includes a cast layer showing a cast structure, and the cast layer is connected to the first transition layer. This composite structure combines the titanium alloy and the light metal material through the intermediate layer, so that the connection strength of the light metal material and the titanium alloy is relatively high. Thereby, the overall strength of the composite structure is improved. The present application also provides a terminal shell, a composite structure preparation method and a shell preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and in particular to a composite structure, a terminal shell, a composite structure preparation method, and a shell preparation method. Background Art

[0002] In the prior art, there is a method of compounding titanium alloy and aluminum alloy or magnesium alloy by roll-bonding. The compounding temperature is 300-350°C, and the interface shear strength is about 85MPa. After solution heat treatment, although the strength of the aluminum alloy or magnesium alloy is significantly improved, the interface shear strength drops sharply. The composite structure formed in this way has poor thermal stability of the bonding interface. Before roll-bonding, no intermediate layer is formed at the interface. After heat treatment, an intermediate layer is formed at the interface. The intermediate layer is formed during solution heat treatment, and the interface intermediate layer formed by solid-solid thermal diffusion leads to a decrease in the interface shear strength. Summary of the invention

[0003] The present application provides a composite structure, a terminal shell, a composite structure preparation method and a shell preparation method, which are convenient for providing a shell structure with high interface shear strength and high yield strength of lightweight metal materials.

[0004] The first aspect of the embodiment of the present application provides a composite structure, including a titanium alloy, a light metal material, and an intermediate layer. The intermediate layer is formed between the titanium alloy and the light metal material. The light metal material includes an aluminum metal material or a magnesium metal material. From the side close to the light metal material to the side close to the titanium alloy, the intermediate layer includes a first transition layer, a stabilization layer, and a second transition layer in sequence. In the first transition layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the first transition layer is |K L-1 |>30% / μm. In the second transition layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the second transition layer |K L-2 |>45% / μm. In the stabilization layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the stabilization layer |K L-w |<15% / μm. The light metal element is the metal element with the highest content in the light metal material. The light metal material comprises a cast layer showing a cast structure, and the cast layer is connected to the first transition layer.

[0005] This composite structure combines titanium alloy and light metal material through the middle layer, so that the connection strength of light metal material and titanium alloy is relatively high. The composition changes of the first transition layer, the stabilization layer and the second transition layer are limited to the above range, which can improve the interface shear strength between the middle layer and the titanium alloy, improve the interface shear strength between the middle layer and the light metal material, and improve the strength of the middle layer itself. Thereby, the overall strength of the composite structure is improved.

[0006] Based on the first aspect, in a possible implementation manner, a thickness of at least one of the first transition layer, the stabilization layer, and the second transition layer is in the range of 0.1-3 μm.

[0007] The thickness of the first transition layer, the stabilization layer and the second transition layer in this composite structure is controlled between 0.1-3 μm, so that the intermediate layer can make the composite structure have sufficient strength, and the time for forming the intermediate layer does not need to be too long.

[0008] Based on the first aspect, in a possible implementation, one side of the intermediate layer is directly connected to the lightweight metal material, and the other side is directly connected to the titanium alloy, the interface shear strength between the intermediate layer and the titanium alloy is ≥55Mpa, and the interface shear strength between the intermediate layer and the lightweight metal material is ≥55Mpa.

[0009] Controlling the interface shear strength between titanium alloy and lightweight metal materials in this composite structure can improve the overall strength of the composite structure and expand the application scenarios of the composite structure.

[0010] Based on the first aspect, in a possible implementation manner, the mass fraction ratio of the light metal element to the titanium element in the first transition layer is greater than 1. The mass fraction ratio of the light metal element to the titanium element in the second transition layer is less than 1.

[0011] In this composite structure, controlling the mass fraction ratio of the light metal element and the titanium element in the first transition layer and the second transition layer can significantly increase the interface shear strength between the first transition layer and the light metal material, and increase the interface shear strength between the second transition layer and the titanium alloy.

[0012] Based on the first aspect, in a possible implementation manner, the titanium alloy is a frame structure having a receiving cavity, and the lightweight metal material is disposed in the receiving cavity.

[0013] In this composite structure, the titanium alloy of the frame structure surrounds the lightweight metal material, forming a composite structure with ultra-high strength on the periphery, light weight in the middle, and sufficient overall strength.

[0014] Based on the first aspect, the lightweight metal material includes an aluminum metal material or a magnesium metal material. The aluminum metal material includes an aluminum alloy or an aluminum-based composite material obtained by adding a reinforcing phase to an aluminum alloy as a matrix. The magnesium metal material includes a magnesium alloy or a magnesium-based composite material obtained by adding a reinforcing phase to a magnesium alloy as a matrix. Among them, the aluminum alloy is an alloy with an aluminum mass fraction greater than 50%; the magnesium alloy is an alloy with a magnesium mass fraction greater than 50%; the added reinforcing phase includes ceramics, carbon nanotubes, graphene, and carbon fiber.

[0015] In this composite structure, the lightweight metal material has aluminum or magnesium as the main component, which reduces the density of the lightweight metal material and reduces the overall weight of the composite structure.

[0016] Based on the first aspect, in a possible implementation, the lightweight metal material includes any one of a 2-series aluminum alloy, a 4-series aluminum alloy, a 6-series aluminum alloy, a 7-series aluminum alloy, a die-cast aluminum alloy, and a die-cast magnesium alloy.

[0017] In this composite structure, 2 series aluminum alloy, 4 series aluminum alloy, 6 series aluminum alloy, 7 series aluminum alloy, die-cast aluminum alloy and die-cast magnesium alloy can be strengthened by heat treatment. The lightweight metal material formed by melting and casting 2 series aluminum alloy, 4 series aluminum alloy, 6 series aluminum alloy, 7 series aluminum alloy, die-cast aluminum alloy and die-cast magnesium alloy has a high yield strength.

[0018] A second aspect of the embodiment of the present application provides a terminal housing, comprising the composite structure provided in the first aspect. The lightweight metal material is provided with an installation groove, and the installation groove is used to place terminal components.

[0019] In this terminal housing, terminal components can be placed in the installation groove, and the terminal housing formed by the composite structure can provide protection for the terminal components.

[0020] Based on the second aspect, in a possible implementation, the titanium alloy is a frame structure having a receiving cavity, the light metal material is disposed in the receiving cavity, and the light metal material is provided with the mounting groove.

[0021] In this terminal housing, the outer titanium alloy is used to improve the external strength of the terminal housing. The light metal material reduces the weight of the terminal housing, and the light metal material is provided with an installation groove, which also facilitates the processing of the installation groove.

[0022] The third aspect of the embodiment of the present application provides a composite structure preparation method, which is used to prepare the composite structure provided in the first aspect, comprising: contacting the surface of the titanium alloy with a molten light metal material. Maintaining the surface contact between the molten light metal material and the titanium alloy, forming the intermediate layer through solid-liquid diffusion at the interface between the molten light metal material and the titanium alloy.

[0023] In this composite structure preparation method, the surface of the titanium alloy is contacted with the molten light metal material, the interface between the molten light metal material and the titanium alloy is controlled to be in a solid-liquid diffusion state, and the composite structure of the first aspect is formed by the diffusion and combination of the light element and the titanium element, thereby improving the overall strength of the composite structure.

[0024] Based on the third aspect, in a possible implementation, the step of bringing the surface of the titanium alloy into contact with the molten light metal material includes: providing a light metal material substrate and a titanium alloy substrate, and bringing the light metal material substrate close to the titanium alloy substrate.

[0025] The light metal material substrate is heated to form the molten light metal material in the contact interface region between the light metal material substrate and the titanium alloy substrate.

[0026] Through this composite structure preparation method, the lightweight metal material does not need to be melted as a whole, but only the part of the lightweight metal material close to the titanium alloy is melted. The generated molten lightweight metal material and the titanium alloy diffuse through solid-liquid diffusion, so that the lightweight elements and titanium elements diffuse and combine with each other, thereby improving the overall strength of the composite structure.

[0027] Based on the third aspect, in a possible implementation, in the step of bringing the surface of the titanium alloy into contact with the molten lightweight metal material, the titanium alloy includes: the titanium alloy is a frame structure having a containing cavity.

[0028] The molten light metal material is injected into the accommodating cavity.

[0029] This composite structure preparation method forms a light metal material and an intermediate layer after the molten light metal material solidifies. The light metal material formed by the solidification of the molten light metal material can be a cast structure as a whole, that is, the light metal material forms a cast layer as a whole, which can improve the overall strength of the light metal material.

[0030] Based on the third aspect, in a possible implementation manner, the titanium alloy has a wall thickness, and the wall thickness is greater than 0.3 mm.

[0031] In this composite structure preparation method, a titanium alloy with a larger wall thickness is used, so that the titanium alloy can absorb a large amount of heat from the molten lightweight metal material, slow down the solidification rate of the molten aluminum alloy, and help the lightweight metal material improve its yield strength.

[0032] Based on the third aspect, in a possible implementation, before the step of injecting the molten lightweight metal material into the accommodating cavity, the method includes: placing the titanium alloy portion in a crystallizer.

[0033] The step of injecting the molten light metal material into the accommodating cavity includes: the accommodating cavity has an opening, and the molten light metal material is injected into the accommodating cavity from the opening.

[0034] The step of maintaining the surface contact between the molten light metal material and the titanium alloy includes: stretching the titanium alloy to move in the crystallizer so that the accommodating cavity gradually passes through the crystallizer from one end away from the opening to the end close to the opening.

[0035] Through this composite structure preparation method, the molten light metal material first injected into the accommodating cavity is first solidified through the crystallizer. By gradually solidifying the molten light metal material, the molten light metal material located in the crystallizer part can be compensated for by the molten light metal material near the opening. On the one hand, the melting and casting effect of the light metal material can be increased, and on the other hand, an intermediate layer can be formed on the periphery of the light metal material, thereby increasing the shear strength of the composite structure.

[0036] Based on the third aspect, in a possible implementation, the molten light metal material is a molten aluminum alloy. The step of injecting the molten light metal material into the accommodating cavity includes: controlling the temperature of the molten aluminum alloy to be between 620-750°C when entering the accommodating cavity.

[0037] The step of maintaining the contact between the molten light metal material and the surface of the titanium alloy includes: controlling the contact time between the molten aluminum alloy and the surface of the titanium alloy to be between 1 and 60 minutes.

[0038] Through this composite structure preparation method, since the molten aluminum alloy will not solidify instantly in large quantities after being injected into the accommodating cavity, the molten aluminum alloy can be placed close to the titanium alloy, and the molten aluminum alloy and the titanium alloy can have sufficient time for solid-liquid diffusion, so that the middle layer has a reasonable element distribution, thereby improving the shear strength of the composite structure.

[0039] Based on the third aspect, in a possible implementation method, in the step of maintaining the surface contact between the molten light metal material and the titanium alloy to control the solidification of the molten aluminum water, it includes: controlling the solidification time of the surface contact between the molten aluminum alloy and the titanium alloy to be between 10-30 minutes.

[0040] By using this composite structure preparation method, the solid-liquid diffusion time of the molten aluminum alloy and titanium alloy is increased.

[0041] Based on the third aspect, in a possible implementation, the light metal material is a 6-series aluminum alloy, and the step of injecting the molten light metal material into the accommodating cavity includes: controlling the temperature of the molten aluminum alloy to be between 700-740° C. when entering the accommodating cavity. Alternatively, the light metal material is a 7-series aluminum alloy, and the step of injecting the molten light metal material into the accommodating cavity includes: controlling the temperature of the molten aluminum alloy to be between 730-750° C. when entering the accommodating cavity.

[0042] In this composite structure preparation method, different temperature controls are adopted according to the specific properties of 6 series aluminum alloy and 7 series aluminum alloy, so that the prepared composite structure has higher shear strength.

[0043] Based on the third aspect, in a possible implementation, before the step of injecting the molten lightweight metal material into the accommodating cavity, the method includes: placing the titanium alloy in a die-casting mold.

[0044] The composite structure preparation method prepares the composite structure in the form of die casting, thereby improving the preparation speed of the composite structure.

[0045] Based on the third aspect, in a possible implementation manner, the molten lightweight metal material is a molten aluminum alloy.

[0046] The step of injecting the molten light metal material into the containing cavity includes: controlling the temperature of the molten aluminum alloy to be between 620° C. and 690° C. when the molten aluminum alloy enters the containing cavity.

[0047] The step of maintaining the contact between the molten light metal material and the surface of the titanium alloy includes: controlling the temperature of the die-casting mold to be between 200-400°C.

[0048] This composite structure preparation method controls the injection temperature of the molten aluminum alloy and the temperature of the die-casting mold so that the molten aluminum alloy is close to the titanium alloy. The molten aluminum alloy and the titanium alloy have sufficient time for solid-liquid diffusion, thereby making the middle layer have a reasonable element distribution and improving the shear strength of the composite structure.

[0049] Based on the third aspect, in a possible implementation method, in the step of maintaining surface contact between the molten light metal material and the titanium alloy, the step includes: controlling the molten light metal material to solidify in the titanium alloy, first cooling it with the mold to below 530°C, and then demolding and cooling it to room temperature to form the light metal material.

[0050] This composite structure preparation method takes the solidified lightweight metal material out of the die-casting mold and then cools it to room temperature, which can accelerate the die-casting process.

[0051] Based on the third aspect, in a possible implementation, the molten light metal material is a molten magnesium alloy. The step of injecting the molten light metal material into the accommodating cavity includes: maintaining the molten magnesium alloy in an inert atmosphere.

[0052] In the composite structure preparation method, the probability of magnesium alloy oxidation is reduced by an inert atmosphere, thereby preparing a composite structure formed by a magnesium alloy, a titanium alloy and an intermediate layer.

[0053] Based on the third aspect, in a possible implementation, in the step of injecting the molten light metal material into the containing cavity, the step includes: controlling the temperature of the molten magnesium alloy to be between 680° C. and 730° C. when the molten magnesium alloy enters the containing cavity.

[0054] The step of maintaining the contact between the molten light metal material and the surface of the titanium alloy includes: controlling the contact time between the molten magnesium alloy and the surface of the titanium alloy to be between 1 and 60 minutes.

[0055] In this composite structure preparation method, since the molten magnesium alloy will not solidify instantly in large quantities after being injected into the accommodating cavity, the molten magnesium alloy can be placed close to the titanium alloy, and the molten magnesium alloy and the titanium alloy can have sufficient time for solid-liquid diffusion, so that the middle layer has a reasonable element distribution, thereby improving the shear strength of the composite structure.

[0056] Based on the third aspect, in a possible implementation, in the step of maintaining the surface contact between the molten light metal material and the titanium alloy, the step includes: controlling the surface contact time between the molten magnesium alloy and the titanium alloy to be between 10-30 minutes.

[0057] By using this composite structure preparation method, the solid-liquid diffusion time of the molten aluminum alloy and titanium alloy is increased.

[0058] Based on the third aspect, in a possible implementation, in the step of injecting the molten light metal material into the accommodating cavity, the step includes: controlling the temperature of the molten magnesium alloy to be between 680-730° C. when entering the accommodating cavity. In the step of maintaining surface contact between the molten light metal material and the titanium alloy, the step includes: controlling the temperature of the die-casting mold to be between 200-400° C.

[0059] This composite structure preparation method controls the injection temperature of the molten magnesium alloy and the temperature of the die-casting mold so that the molten magnesium alloy is close to the titanium alloy. The molten magnesium alloy and the titanium alloy have sufficient time for solid-liquid diffusion, thereby making the middle layer have a reasonable element distribution and improving the shear strength of the composite structure.

[0060] A fourth aspect of the embodiments of the present application provides a shell preparation method for preparing the terminal shell of the second aspect. The shell preparation method is based on the composite structure prepared by the composite structure preparation method provided in the third aspect, and includes:

[0061] The composite structure is heat treated and shaped to form a blank.

[0062] The installation groove and the outer dimensions are processed on the blank.

[0063] The blank is surface treated to form the terminal housing.

[0064] The heat treatment includes aging heat treatment.

[0065] The aging heat treatment is performed after the step of shaping the blank.

[0066] By performing aging heat treatment on the composite structure, the yield strength and shear strength of the material can be improved; if solution heat treatment is performed before aging heat treatment, the yield and shear strength of the material can be improved more effectively. Aging heat treatment can not only improve the yield and shear strength of the material, but also reduce the internal stress of the material.

[0067] By machining and setting the mounting groove on the formed blank, the terminal components can be placed in the mounting groove, and the terminal housing provides protection for the terminal components.

[0068] Based on the fourth aspect, in a possible implementation, in the step of heat treating and shaping the composite structure to form a blank, the composite structure is heated to a solid solution temperature and kept at the solid solution temperature for a solid solution time. The solid solution temperature is 490-540°C, or 500-550°C, or 480-540°C, or 390-460°C. The fixing time is 30-300 minutes.

[0069] In this shell preparation method, different solution temperatures can be selected for different lightweight metal materials. Specifically, 6 series aluminum alloy can adopt a solution temperature of 490-540°C. 7 series aluminum alloy can adopt a solution temperature of 500-550°C. Die-cast aluminum alloy can adopt a solution temperature of 480-540°C. Die-cast magnesium alloy can adopt a solution temperature of 390-460°C. The prepared terminal shell has higher shear strength.

[0070] Based on the fourth aspect, in a possible implementation, in the step of heat treating and shaping the composite structure to form a blank, the step includes: heating the composite structure to an aging temperature, and maintaining the temperature at the aging temperature for an aging time. The aging temperature is 170-200°C, or 110-150°C, or 150-180°C, or 140-180°C. The fixing time is 30-300 minutes.

[0071] In this shell preparation method, different aging temperatures can be selected for different lightweight metal materials. Specifically, 6 series aluminum alloys can adopt an aging temperature of 170-200°C. 7 series aluminum alloys can adopt an aging temperature of 110-150°C. Die-cast aluminum alloys can adopt an aging temperature of 150-180°C. Die-cast magnesium alloys can adopt an aging temperature of 140-180°C. This makes the prepared terminal shell have higher shear strength.

[0072] Through this shell preparation method, the solid solution effect of aluminum alloy and titanium alloy is enhanced.

[0073] Based on the fourth aspect, in a possible implementation, the titanium alloy is a frame structure having a receiving cavity, the lightweight metal material is located in the receiving cavity, and the receiving cavity extends along a first direction. Before the step of processing the blank into the mounting groove and the outer dimensions, the step further includes: cutting the composite structure or the blank so that the size of the composite structure or the blank after cutting in the first direction reaches a preset size corresponding to the terminal housing.

[0074] By means of this shell preparation method, a composite structure having a relatively large size in the first direction can be prepared in advance. The composite structure can be first cut into a plurality of composite structures having a preset size corresponding to the terminal shell, and then heat treated and shaped to form a blank. Alternatively, the composite structure can be first heat treated and shaped to form a blank, and then the blank can be cut into a plurality of blanks having a preset size corresponding to the terminal shell. The heat treatment process includes aging heat treatment. In this way, a composite structure having a relatively large volume can be prepared at one time, and the composite structure can be used to prepare a plurality of terminal shells.

[0075] Based on the fourth aspect, in a possible implementation, the step of processing the blank to form the installation groove and the outer dimensions further includes: machining the blank to form the installation groove and the outer dimensions using a machining method.

[0076] This shell preparation method processes the installation groove and the outer dimensions through machining, and has high machining accuracy.

[0077] Based on the fourth aspect, in a possible implementation, the step of processing the blank to form the installation groove and the outer dimensions further includes performing glue drawing or nano injection molding on the blank.

[0078] This shell preparation method forms a plastic area on a part of the metal surface by glue drawing or nano injection molding. The plastic area can insulate the terminal components located in the installation groove or serve as the antenna seam of the terminal shell, and has better corrosion resistance.

[0079] Based on the fourth aspect, in a possible implementation, the surface treatment includes: polishing or coating the surface of the blank with a film layer or sandblasting or brushing.

[0080] This shell preparation method can increase the aesthetics of the terminal shell through surface treatment, and also improve the corrosion resistance of the terminal shell. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0082] Figure 2 A schematic structural diagram of a composite structure in one embodiment of the present application is shown.

[0083] Figure 3 A local cross-section diagram of a composite structure obtained by cooling a crystallizer in one embodiment of the present application is shown.

[0084] Figure 4 A local slice diagram of a composite structure obtained by a composite structure preparation method in one embodiment of the present application is shown.

[0085] Figure 5 The figure shows a temperature variation curve of a molten aluminum alloy (lightweight metal material) in one embodiment of the present application.

[0086] Figure 6 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0087] Figure 7 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0088] Figure 8 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0089] Fig. 9 A schematic structural diagram of a composite structure in one embodiment of the present application is shown.

[0090] Fig.10 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0091] Fig.11 A flow chart of a shell preparation method in one embodiment of the present application is shown.

[0092] Main component symbols

[0093] Titanium Alloy 100

[0094] Lightweight metal materials 200

[0095] Aluminum Alloy 200a

[0096] Magnesium alloy 200b

[0097] Accommodating chamber 101

[0098] Middle layer 300

[0099] First direction X

[0100] The following specific implementation methods will further illustrate the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION

[0101] The following specific embodiments illustrate the implementation of the present application, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Although the description of the present application will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this application are limited to the implementation. On the contrary, the purpose of introducing the application in conjunction with the implementation is to cover other options or modifications that may be extended based on the claims of the present application. In order to provide a deep understanding of the present application, the following description will include many specific details. The present application can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present application, some specific details will be omitted in the description. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0102] Hereinafter, if used, the terms "first", "second", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise specified, "plurality" means two or more. Positional terms such as "upper", "lower", "left", and "right" are defined relative to the orientation of the components schematically placed in the accompanying drawings. It should be understood that these directional terms are relative concepts. They are used for description and clarification relative to the components, and may change accordingly according to changes in the orientation of the components placed in the accompanying drawings.

[0103] In this application, if used, unless otherwise expressly specified and limited, the term "connection" should be understood in a broad sense, for example, "connection" can be fixed connection, detachable connection, or integrated; can be directly connected or indirectly connected through an intermediate medium. The term "and / or" used herein includes any and all combinations of one or more of the relevant listed items.

[0104] When the following embodiments are described in detail in conjunction with schematic diagrams, for ease of explanation, the diagrams showing the local structures of the devices will not be partially enlarged according to the general scale, and the schematic diagrams are only examples and should not limit the scope of protection of this application.

[0105] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below in conjunction with the accompanying drawings.

[0106] Embodiment 1

[0107] Figure 1 A flow chart of a method for preparing a shell in one embodiment of the present application is shown, in which the lightweight metal material 200 is an aluminum alloy 200a.

[0108] like Figure 1 As shown, the shell preparation method includes:

[0109] S100, preparing a composite structure by a composite structure preparation method.

[0110] S200, processing the composite structure to form a terminal housing.

[0111] The composite structure preparation method includes:

[0112] S110, bringing the surface of the titanium alloy 100 into contact with the molten aluminum alloy.

[0113] S120 , maintaining surface contact between the molten aluminum alloy and the titanium alloy 100 , and forming the intermediate layer 300 through solid-liquid diffusion at the interface between the molten aluminum alloy and the titanium alloy 100 .

[0114] In step S110, the step of preparing the titanium alloy 100 is also included:

[0115] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer circumference of the titanium alloy 100 is 155 mm and the width is 85 mm. The inner wall of the accommodating cavity 101 is 149 mm long and 79 mm wide, that is, the wall thickness of the titanium alloy 100 is 3 mm. The size of the titanium alloy 100 in the first direction X is 200 mm.

[0116] It is understandable that as the wall thickness of the titanium alloy 100 decreases, the solidification time of the molten aluminum alloy will be appropriately shortened. The wall thickness of the titanium alloy 100 is preferably greater than 0.3 mm.

[0117] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0118] S1113, partially placing the titanium alloy 100 in the crystallizer. The first direction X is a vertical direction, an end of the titanium alloy 100 facing away from the opening is located in the crystallizer, and the opening of the titanium alloy 100 is located above the crystallizer.

[0119] The size of the accommodating cavity 101 reaches 149×79 mm, which increases the amount of molten aluminum alloy stored in the accommodating cavity 101, thereby slowing down the solidification process of the molten aluminum alloy in the accommodating cavity 101, extending the solidification time of the molten aluminum alloy, allowing sufficient solid-liquid diffusion and bonding at the titanium-aluminum interface, and increasing the interface bonding strength.

[0120] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten aluminum alloy in the accommodating cavity 101 in step S120 , the aluminum element diffuses and reacts with the titanium element.

[0121] The cooperation between the crystallizer and the titanium alloy 100 prepares for the subsequent solidification of the molten aluminum alloy.

[0122] In step S110, the step of preparing molten aluminum alloy is also included:

[0123] S1121, preparing 7075 aluminum alloy as an aluminum material, melting the aluminum material, and forming a molten aluminum alloy.

[0124] On the one hand, 7075 aluminum alloy has high strength, and on the other hand, it has heat treatment strengthening properties, which can further enhance the mechanical properties during subsequent heat treatment.

[0125] In step S110, the step of controlling the initial temperature of the molten aluminum alloy is also included:

[0126] S1131, controlling the temperature of the molten aluminum alloy injected into the receiving cavity 101 to be 730-750°C.

[0127] Corresponding to the above-mentioned size of the containing cavity 101, the temperature of the molten aluminum alloy is controlled to be in the range of 730-750°C, which can effectively control the yield strength of the final aluminum alloy 200a to be above 150 MPa.

[0128] In step S120, it also includes:

[0129] S121, the drawn titanium alloy 100 moves in the crystallizer, so that the accommodating cavity 101 gradually passes through the crystallizer from the end away from the opening to the end close to the opening. The speed of drawing the titanium alloy 100 is controlled so that the solidification time of each local molten aluminum alloy in the titanium alloy 100 is between 8-10 minutes. Through the solid-liquid diffusion at the interface of the molten aluminum alloy and the titanium alloy 100, the diffusion and combination of the titanium element and the aluminum element in the intermediate layer 300 are achieved.

[0130] S122, after the overall temperature of the composite structure is reduced to below 530°C, the composite structure is water-cooled to room temperature, thereby controlling the structural composition of the middle layer 300 and ensuring the strength of the middle layer 300.

[0131] In step S121, the solidification speed of the molten aluminum alloy is controlled by the drawing speed, which can effectively ensure the yield strength of the aluminum alloy after solidification. At the same time, the titanium element and the aluminum element can be fully diffused and combined, so that the intermediate layer 300 forms a reasonable element distribution.

[0132] In step S122 , the grain size of the aluminum alloy 200 a is controlled by water cooling, and the structural composition of the intermediate layer 300 is controlled to ensure the strength of the intermediate layer 300 .

[0133] After all the molten aluminum alloy solidifies, an integral aluminum alloy 200a is formed. The entire aluminum alloy 200a is a cast layer showing a cast structure. The aluminum alloy 200a of the cast structure has coarse grains, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the aluminum alloy 200a has a higher strength. In addition, the cast structure has a higher connection strength with the intermediate layer 300.

[0134] It is understandable that when the aluminum material is not 7075 aluminum alloy, the temperature of the molten aluminum alloy injected into the accommodating cavity 101 will be adjusted accordingly. For example, when 6013 aluminum alloy or 6063 aluminum alloy is used, the temperature of the molten aluminum alloy injected into the accommodating cavity 101 can be controlled at 700-740° C. When other die-casting aluminum alloys are used, the temperature of the molten aluminum alloy injected into the accommodating cavity 101 can also be controlled below 700° C.

[0135] Figure 2 A schematic structural diagram of a composite structure in one embodiment of the present application is shown. Figure 3 A local metallographic image of a composite structure obtained by cooling a crystallizer in one embodiment of the present application is shown, and the scale in the image is 4 μm for each scale distance.

[0136] like Figure 2 and Figure 3As shown, the composite structure includes a titanium alloy 100, an aluminum alloy 200a and an intermediate layer 300. The intermediate layer 300 is formed during the solidification and cooling process of the molten aluminum alloy and is located between the aluminum alloy 200a and the titanium alloy 100.

[0137] The interface shear strength of the intermediate layer 300 reaches 80 MPa. The interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥ 80 MPa, and the interface shear strength between the intermediate layer 300 and the aluminum alloy 200a is ≥ 80 MPa. The yield strength of the aluminum alloy 200a reaches 150 MPa, and the elongation reaches 8%. The hardness of the titanium alloy 100 reaches 450 Hv.

[0138] Figure 4 A local slice diagram of a composite structure obtained by a composite structure preparation method in one embodiment of the present application is shown.

[0139] like Figure 4 As shown, in this composite structure, the intermediate layer 300 includes a first transition layer, a stabilization layer and a second transition layer.

[0140] The first transition layer is the portion of the intermediate layer 300 close to the aluminum alloy 200a. In terms of morphology, the first transition layer is similar to the aluminum alloy 200a, but a titanium-aluminum solid solution has appeared in the composition of the first transition layer. The thickness of the first transition layer is between 0.1-3μm. The thickness is the size from the titanium alloy 100 to the aluminum alloy 200a. If the intermediate layer 300 is roughly regarded as a plane, the thickness is the size in the direction perpendicular to the plane where the intermediate layer 300 is located. During the solidification of the molten aluminum alloy and the cooling of the aluminum alloy 200a, the titanium element in the titanium alloy 100 diffuses into the aluminum alloy 200a and realizes solid solution to form the first transition layer. In the first transition layer, the mass fraction ratio of the aluminum element to the titanium element is greater than 1. Moreover, from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100, the mass fraction of the aluminum element tends to decrease.

[0141] right Figure 4 Selecting four points A, B, C, and D from the slice diagram for component analysis yields the data in Table 1.

[0142] Table 1 Slice image component analysis results

[0143] Position (μm) Al mass fraction (%) A 1 80 B 1.8 53 C 3 38 D 3.8 0

[0144] As shown in Table 1, according to the quantitative analysis of Al elements at points A and B, in the first transition layer, along the thickness direction, the average change rate of the mass fraction of the aluminum element |K Al-1|=34% / μm. The average change rate of the mass fraction of aluminum element shows a linear downward trend along the thickness direction. In the first transition layer, the change rate of the mass fraction of aluminum element at any two points with a spacing of 0.2μm along the thickness direction is within |K Al-1 |=(28-40)% / μm. However, due to the natural diffusion characteristics of aluminum and titanium, there may be a situation where the mass fraction of aluminum changes extremely or extremely slowly between two points with a very small interval along the thickness direction. The actual composite structure has a certain composition error, and there is also a certain error in the position of the composition analysis. The average change rate of the mass fraction of aluminum in the first transition layer |K Al-1 |>30% / μm, the shear strength at the first transition layer can be high enough. The components in the first transition layer transition smoothly, so that the connection strength between the aluminum alloy 200a and each position of the first transition layer is strong, ensuring the shear strength between the aluminum alloy 200a and the intermediate layer 300.

[0145] It can be understood that in the first transition layer, the mass fraction of the aluminum element shows a decreasing trend from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100. However, it may appear that the mass fraction of the aluminum element slightly increases and then decreases from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100 in a local position. This does not affect the overall decreasing trend of the mass fraction of the aluminum element.

[0146] The second transition layer is the portion of the intermediate layer 300 close to the titanium alloy 100. The thickness of the second transition layer is between 0.1-3 μm. During the solidification of the molten aluminum alloy and the cooling of the aluminum alloy 200a, the aluminum element diffuses into the titanium alloy 100 and realizes solid solution to form the second transition layer. In the second transition layer, the mass fraction ratio of the aluminum element to the titanium element is less than 1. Moreover, the mass fraction of the aluminum element tends to decrease from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100.

[0147] As shown in Table 1, according to the quantitative analysis of Al element at points C and D, in the second transition layer, along the thickness direction, the average change rate of the mass fraction of aluminum element |K Al-2 |=48% / μm. The average change rate of the mass fraction of aluminum element shows a linear downward trend along the thickness direction. In the second transition layer, the change rate of the mass fraction of aluminum element at any two points with a spacing of 0.2μm along the thickness direction is within |K Al-2|=(40-55)% / μm. However, due to the natural diffusion characteristics of aluminum and titanium, there may be a situation where the mass fraction of aluminum changes extremely or extremely slowly between two points with a very small interval along the thickness direction. The actual composite structure has a certain composition error, and there is also a certain error in the position of the composition analysis. The average change rate of the mass fraction of aluminum in the first transition layer |K Al-2 |>45% / μm, the shear strength at the second transition layer can be high enough. The components in the second transition layer transition smoothly, so that the connection strength between the titanium alloy 100 and each position of the second transition layer is strong, ensuring the shear strength between the titanium alloy 100 and the intermediate layer 300.

[0148] It can be understood that in the second transition layer, the mass fraction of the aluminum element shows a decreasing trend from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100. However, it may appear that the mass fraction of the aluminum element slightly increases and then decreases from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100 in a local position. This does not affect the overall decreasing trend of the mass fraction of the aluminum element.

[0149] The stabilizing layer is located between the first transition layer and the second transition layer. The morphology of the stabilizing layer is obviously different from that of the aluminum alloy 200a. The thickness of the stabilizing layer is between 0.1-3 μm.

[0150] As shown in Table 1, according to the quantitative analysis of Al element at points B and C, from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100, in the stable layer, along the thickness direction, the average change rate of the mass fraction of the aluminum element | K Al-w |=13% / μm. The average change rate of the mass fraction of aluminum element shows a linear downward trend along the thickness direction. In the second transition layer, the change rate of the mass fraction of aluminum element is within |K when any two points with a spacing of 0.2μm are selected along the thickness direction. Al-w |=(7-20)% / μm. However, due to the natural diffusion characteristics of aluminum and titanium, there may be a situation where the mass fraction of aluminum changes extremely or extremely slowly between two points with a very small interval along the thickness direction. The actual composite structure produced has a certain composition error, and there is also a certain error in the position according to the composition analysis. The average change rate of the mass fraction of aluminum in the first transition layer |K Al-w |<15% / μm, the shear strength at the stable layer can be high enough.

[0151] It can be understood that in the second transition layer, the mass fraction of the aluminum element shows a decreasing trend from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100. However, it may appear that the mass fraction of the aluminum element slightly increases and then decreases from the side close to the aluminum alloy 200a to the side close to the titanium alloy 100 in a local position. This does not affect the overall decreasing trend of the mass fraction of the aluminum element.

[0152] The stabilizing layer of the aluminum intermediate layer has a relatively stable component distribution, and the intermediate layer 300 formed by the first transition layer, the stabilizing layer, and the second transition layer can maintain the same interface shear strength or negligible attenuation even after being heated at a high temperature again. Therefore, the composite structure can be heat-treated again in subsequent processing, and maintain a high interface shear strength after the heat treatment.

[0153] It is understandable that the thickness of the first transition layer, the second transition layer and the stabilization layer are all controlled within 0.1-3 μm, which makes it easier to form the intermediate layer 300 under the premise of having sufficient strength. If the thickness of any one of the first transition layer, the second transition layer and the stabilization layer is greater than 3 μm, although the strength of the intermediate layer 300 is still sufficient, the formation time will be relatively prolonged. If the thickness of any one of the first transition layer, the second transition layer and the stabilization layer is less than 0.1 μm, although the intermediate layer 300 can be formed quickly, the strength of the intermediate layer 300 may not meet the use requirements.

[0154] It is understandable that the titanium alloy 100 may not adopt a frame structure. For example, according to actual use requirements, the titanium alloy 100 is set to a plate structure, and a chamber is formed by setting an auxiliary device outside the titanium alloy, and the molten aluminum alloy is injected into the chamber so that the molten aluminum alloy contacts the titanium alloy, and the solidification of the molten aluminum alloy is controlled so that the molten aluminum alloy forms an aluminum alloy 200a with sufficient yield strength, and forms an intermediate layer 300.

[0155] Please return to Figure 1 , the process of processing the composite structure to form the terminal housing includes:

[0156] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0157] S220, shaping and heat treating the composite structure to form a blank.

[0158] S230, processing the installation groove and the outer dimensions on the blank.

[0159] S240, surface treating the blank to form a terminal housing.

[0160] In step S210, the preset size can be adjusted according to the terminal shell. For example, the preset size is 1-2 mm larger than the final size of the terminal shell. In the first direction X, the size of the finished terminal shell is 8 mm, and the size loss caused by further cutting, shaping and compression of the composite structure in subsequent processing can be considered, and the preset size can be set to 9-10 mm.

[0161] In step S220, it includes:

[0162] S221, grinding of composite structures to remove burrs.

[0163] S222, solution heat treatment is performed on the composite structure. It includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is between 500-550°C, and the solution time is between 30-300 minutes. In this process, the strength of the aluminum alloy 200a can be further improved. After the composite structure is heated to 500-550°C, it is kept warm for 30-50 minutes to obtain a composite structure with a certain improvement in the strength of the aluminum alloy 200a. Controlling the solution time to 30-50 minutes can save preparation time.

[0164] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0165] S224, performing aging heat treatment on the composite structure. Specifically, the composite structure is kept at 110-150°C for 4-10 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the aluminum alloy 200a.

[0166] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to aging heat treatment.

[0167] It is understandable that when the aluminum material does not use 7075 aluminum alloy, the solution temperature can be adjusted. For example, when 6013 aluminum alloy or 6063 aluminum alloy is used, the solution temperature can be controlled at 490-540°C. When the aluminum material does not use 7075 aluminum alloy, the temperature of aging heat treatment can also be adjusted. For example, when 6013 aluminum alloy or 6063 aluminum alloy is used, the solution temperature can be controlled at 170-200°C.

[0168] After the treatment of step S220, when the solution time is controlled at 30-50 minutes and the holding time in the aging heat treatment is controlled at 6 hours. The interface shear strength of the composite structure can be further increased to 120 MPa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥120 MPa, and the interface shear strength between the intermediate layer 300 and the aluminum alloy 200a is ≥120 MPa. The yield strength of the aluminum alloy 200a can be further increased to 380 MPa, and the elongation of the aluminum alloy 200a reaches 5%. The hardness of the titanium alloy 100 reaches 420 Hv.

[0169] The shear test of the composite structure before step S220 is compared with the shear test of the composite structure after step S220. The shear ports of both are not in the middle layer 300, but are located at the position of the aluminum alloy 200a close to the middle layer 300. Therefore, the improvement of the interface shear strength in step S220 is caused by the improvement of the yield strength of the aluminum alloy 200a, which ensures the overall strength of the composite structure.

[0170] In step S230, it includes:

[0171] S231, through forging or full CNC (Computerized Numerical Control) machining, the blank is processed to process the installation groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the installation groove and the outer dimensions are more accurate.

[0172] The mounting slot is designed according to the terminal components that are actually required to be installed in the terminal housing, and the external dimensions are determined according to the appearance design of the actual terminal housing.

[0173] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0174] In step S240, it includes:

[0175] S241, coating the surface of the blank with a film layer. The blank after nano injection molding is placed in a PVD (Physical Vapor Deposition) device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0176] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0177] It is understandable that the mounting groove may not be completely formed on the aluminum alloy 200 a , and the mounting groove may be processed and set on both the titanium alloy 100 and the aluminum alloy 200 a .

[0178] Figure 5 FIG. 1 shows a temperature variation curve of a molten aluminum alloy (aluminum alloy 200a ) in one embodiment of the present application.

[0179] like Figure 5 As shown, the molten aluminum alloy enters the titanium alloy 100 at a high temperature and is cooled to solidification through a crystallizer. The composite structure after the molten aluminum alloy solidifies is then taken out of the crystallizer and cooled to room temperature by water cooling. It is then heated to the aluminum solution temperature, maintained for a certain period of time, and then quenched. After quenching, the internal stress of the composite structure is reduced by aging heat treatment.

[0180] It can be understood that in the above process, after the molten aluminum alloy is cooled and solidified by the crystallizer and the composite structure is cooled to room temperature, the intermediate layer 300 has appeared, and the yield strength of the aluminum alloy 200a has reached 150Mpa. The composite structure has met the preparation requirements of the terminal shell, and the composite structure is heated and quenched again in the subsequent step S220 to further strengthen the shear strength of the composite structure and increase the yield strength of the aluminum alloy 200a, which can further enhance the product quality of the terminal shell.

[0181] The method for preparing a shell by using a crystallizer to assist the solidification of a molten aluminum alloy comprises:

[0182] S1111, prepare a square tube-shaped titanium alloy 100, in the cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 155 mm, the width is 85 mm, the inner wall of the accommodating cavity 101 is 149 mm long, and the width is 79 mm, that is, the wall thickness of the titanium alloy 100 is 3 mm. The size of the titanium alloy 100 in the first direction X is 200 mm.

[0183] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0184] S1113, partially placing the titanium alloy 100 in the crystallizer. The first direction X is a vertical direction, an end of the titanium alloy 100 facing away from the opening is located in the crystallizer, and the opening of the titanium alloy 100 is located above the crystallizer.

[0185] S1121, preparing 7075 aluminum alloy as an aluminum material, melting the aluminum material, and forming a molten aluminum alloy.

[0186] S1131, injecting molten aluminum alloy into the containing cavity 101 from the opening, and controlling the temperature of the molten aluminum alloy injected into the containing cavity 101 to be 700-750°C.

[0187] S121, the titanium alloy 100 is stretched and moved in the crystallizer, so that the accommodating cavity 101 gradually passes through the crystallizer from the end away from the opening to the end close to the opening. The speed of the titanium alloy 100 is controlled so that the solidification time of each local molten aluminum alloy in the titanium alloy 100 is between 8-10 minutes.

[0188] S122, after the overall temperature of the composite structure is reduced to below 530°C, the composite structure is water-cooled to room temperature.

[0189] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0190] S221, grinding of composite structures to remove burrs.

[0191] S222, heating the composite structure, keeping the temperature, and then quenching to room temperature. The composite structure is heated to between 500-550°C, kept at the temperature for 30-50 minutes, and then quenched to room temperature.

[0192] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0193] S224, aging heat treatment of the composite structure. The composite structure is kept at 110-150°C for 6 hours.

[0194] S231, through forging or full CNC machining, the blank is processed to have the mounting groove and external dimensions.

[0195] S232, nano-injection molding the inner wall of the installation groove.

[0196] S240, coating a film layer on the surface of the blank.

[0197] It can be understood that the lightweight metal material 200 can not only be aluminum alloy 200a, but can also be replaced by an aluminum-based composite material obtained by adding a reinforcing phase to an aluminum alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0198] Through this shell preparation method, the molten aluminum alloy has a sufficiently long solidification time, and the intermediate layer 300 between the aluminum alloy 200a and the titanium alloy 100 has sufficient shear strength. The growth morphology of the grains of the aluminum alloy 200a itself tends to be columnar crystals, which increases the yield strength of the aluminum alloy 200a, so that the yield strength of the aluminum alloy 200a reaches more than 150Mpa. In the process of heat treating the composite structure, the strength of the composite structure is further increased. After the aluminum alloy 200a and the titanium alloy 100 have sufficient connection strength, the installation groove is processed and set in the aluminum alloy 200a. After the terminal components are placed in the installation groove, the terminal components are protected by the terminal shell.

[0199] Embodiment 2

[0200] Figure 6 The flowchart of the shell manufacturing method in one embodiment of the present application is shown. The light metal material 200 in the shell is aluminum alloy 200a.

[0201] like Figure 6 As shown, the shell preparation method includes:

[0202] S100, preparing a composite structure by a composite structure preparation method.

[0203] S200, processing the composite structure to form a terminal housing.

[0204] The composite structure preparation method includes:

[0205] S110, bringing the surface of the titanium alloy 100 into contact with the molten aluminum alloy.

[0206] S120 , maintaining surface contact between the molten aluminum alloy and the titanium alloy 100 , and forming the intermediate layer 300 through solid-liquid diffusion at the interface between the molten aluminum alloy and the titanium alloy 100 .

[0207] In step S110, the step of preparing the titanium alloy 100 is also included:

[0208] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm long and 84 mm wide, and the inner wall of the accommodating cavity 101 is 154 mm long and 80 mm wide, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0209] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0210] S1113, placing the titanium alloy 100 in a die-casting mold. The first direction X is a horizontal direction, and the molten aluminum alloy is injected into the titanium alloy 100 along the horizontal direction by an injection device.

[0211] The size of the accommodating cavity 101 reaches 160×84 mm, which increases the amount of molten aluminum alloy stored in the accommodating cavity 101, thereby slowing down the solidification process of the molten aluminum alloy in the accommodating cavity 101 and extending the solidification time of the molten aluminum alloy, so that the aluminum alloy 200a has sufficient strength.

[0212] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten aluminum alloy in the accommodating cavity 101 in step S120 , the aluminum element diffuses and reacts with the titanium element.

[0213] The titanium alloy 100 is placed in a die-casting mold to prepare for the subsequent solidification of the molten aluminum alloy.

[0214] In step S110, the step of preparing molten aluminum alloy is also included:

[0215] S1121, prepare ADC12 aluminum alloy as an aluminum material, melt the aluminum material, and form a molten aluminum alloy.

[0216] ADC12 aluminum alloy has high strength on the one hand and heat treatability on the other hand, which can further enhance its performance during subsequent heat treatment.

[0217] In step S110, the step of controlling the initial temperature of the molten aluminum alloy is also included:

[0218] S1131, controlling the temperature of the molten aluminum alloy injected into the accommodating cavity 101 to be between 620°C and 690°C. Controlling the temperature of the die-casting mold to be between 250°C and 300°C.

[0219] In step S120, it also includes:

[0220] S121, the portion of the molten aluminum alloy near the titanium alloy 100 solidifies for more than 1 minute and then cools to 400° C. The titanium element and the aluminum element in the intermediate layer 300 diffuse and combine through solid-liquid diffusion at the interface between the molten aluminum alloy and the titanium alloy 100.

[0221] S122, after the overall temperature of the composite structure is reduced to between 420-480°C, the composite structure is air-cooled to room temperature, thereby controlling the structural composition of the middle layer 300 and ensuring the strength of the middle layer 300.

[0222] Controlling the temperature of the die casting mold in step S121 can control the solidification speed of the molten aluminum alloy, effectively ensuring the yield strength of the aluminum alloy 200a after solidification, and at the same time allowing the titanium element and the aluminum element to fully diffuse and combine, so that the intermediate layer 300 forms a reasonable element distribution.

[0223] In step S122 , the grain size of the aluminum alloy 200 a is controlled by air cooling, and the structural composition of the intermediate layer 300 is controlled to ensure the strength of the intermediate layer 300 .

[0224] After all the molten aluminum alloy solidifies, an integral aluminum alloy 200a is formed. The entire aluminum alloy 200a is a cast layer showing a cast structure. The aluminum alloy 200a of the cast structure has coarse grains, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the aluminum alloy 200a has a higher strength. In addition, the cast structure has a higher connection strength with the intermediate layer 300.

[0225] The composite structure prepared by the above steps has similar metallographic characteristics to the composite structure in Example 1.

[0226] The composite structure prepared by the above steps has an interface shear strength of 60 MPa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥ 60 MPa, and the interface shear strength between the intermediate layer 300 and the aluminum alloy 200a is ≥ 60 MPa. The yield strength of the aluminum alloy 200a reaches 100 MPa, the elongation reaches 4%, and the hardness of the titanium alloy 100 reaches 300 Hv.

[0227] The process of machining the composite structure to form the terminal housing includes:

[0228] S210, cutting the composite structure. Removing the protruding features such as the material head formed when the composite structure is die-cast.

[0229] S220, shaping and heat treating the composite structure to form a blank.

[0230] S230, processing the installation groove and the outer dimensions on the blank.

[0231] S240, surface treating the blank to form a terminal housing.

[0232] In step S220, it includes:

[0233] S221, grinding of composite structures to remove burrs.

[0234] S222, solution heat treatment is performed on the composite structure. It includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is controlled between 480-540°C, and the solution time is between 30-300 minutes. In this process, the strength of aluminum alloy 200a can be further improved. After the composite structure is heated to 500-550°C, it is kept warm for 30-50 minutes to obtain a composite structure with a certain improvement in the strength of aluminum alloy 200a. Controlling the solution time to 30-50 minutes can save preparation time.

[0235] S223, shaping the composite structure. The flatness of the composite structure after flattening can be controlled within 0.3 mm.

[0236] S224, performing aging heat treatment on the composite structure. Specifically, the composite structure is kept at 150-180°C for 4-10 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the aluminum alloy 200a.

[0237] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to aging heat treatment.

[0238] It is understandable that when the composite structure itself has sufficient strength and the composite structure generated by the die-casting process is basically consistent with the external dimensions of the terminal housing, the composite structure can be simply shaped by grinding and removing burrs. Neither solution heat treatment nor large-scale shaping is performed. After the composite structure is simply shaped, the composite structure can be subjected to aging heat treatment to adjust the performance of the composite structure.

[0239] After the processing of step S220, the composite structure is shaped without solution heat treatment, and the temperature in the aging heat treatment is controlled between 165-175°C and kept warm for 5 hours. The interface shear strength of the composite structure can be further improved to 85Mpa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥85Mpa, and the interface shear strength between the intermediate layer 300 and the aluminum alloy 200a is ≥85Mpa. The yield strength of the aluminum alloy 200a can be further improved to 160Mpa, and the elongation of the aluminum alloy 200a reaches 3%. The hardness of the titanium alloy 100 reaches 300Hv.

[0240] In step S230, the blank is processed by forging or full CNC machining to form the mounting groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the mounting groove and make the outer dimensions more accurate.

[0241] The mounting slot is designed according to the terminal components that are actually required to be installed in the terminal housing, and the external dimensions are determined according to the appearance design of the actual terminal housing.

[0242] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0243] In step S240, it includes:

[0244] S241, coating the surface of the blank with a film layer. The blank after nano injection molding is placed in a PVD device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0245] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0246] It is understandable that the mounting groove may not be completely formed on the aluminum alloy 200 a , and the mounting groove may be processed and set on both the titanium alloy 100 and the aluminum alloy 200 a .

[0247] It can be understood that in the above process, after the molten aluminum alloy is cooled and solidified by the crystallizer and the composite structure is cooled to room temperature, the intermediate layer 300 has appeared, and the yield strength of the aluminum alloy 200a has reached 150Mpa. The composite structure has met the preparation requirements of the terminal shell, and the composite structure is heated and quenched again in the subsequent step S220 to further strengthen the shear strength of the composite structure and increase the yield strength of the aluminum alloy 200a, which can further enhance the product quality of the terminal shell.

[0248] A method for preparing a shell by using a die-casting mold to assist the solidification of a molten aluminum alloy, comprising:

[0249] S1111, prepare a square titanium alloy 100, in the cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm, the width is 84 mm, the inner wall of the accommodating cavity 101 is 154 mm long, and the width is 80 mm, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0250] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0251] S1113, placing the titanium alloy 100 in a die-casting mold. The first direction X is a horizontal direction, and the molten aluminum alloy is injected into the titanium alloy 100 along the horizontal direction by an injection device.

[0252] S1121, preparing ADC12 aluminum alloy as an aluminum material, and melting the aluminum material to form a molten aluminum alloy.

[0253] S1131, controlling the temperature of the molten aluminum alloy injected into the accommodating cavity 101 to be between 620°C and 690°C. Controlling the temperature of the die-casting mold to be between 250°C and 300°C.

[0254] S121, the molten aluminum alloy is solidified in the titanium alloy 100 for more than 1 minute and then cooled to 400°C.

[0255] S122, after the overall temperature of the composite structure is reduced to between 420-480°C, the composite structure is air-cooled to room temperature.

[0256] S210, cutting the composite structure. Removing the protruding features such as the material head formed when the composite structure is die-cast.

[0257] S221, grinding of composite structures to remove burrs.

[0258] S222, performing solution heat treatment on the composite structure. S223, shaping the composite structure.

[0259] S224, performing aging heat treatment on the composite structure.

[0260] S231, processing the installation groove and the outer dimensions on the blank.

[0261] S232, nano-injection molding the inner wall of the installation groove.

[0262] S241, coating the surface of the blank with a film layer.

[0263] It can be understood that the lightweight metal material 200 can not only be aluminum alloy 200a, but can also be replaced by an aluminum-based composite material obtained by adding a reinforcing phase to an aluminum alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0264] Through this shell preparation method, the molten aluminum alloy has a sufficiently long solidification time, and the intermediate layer 300 between the aluminum alloy 200a and the titanium alloy 100 has sufficient shear strength. The growth morphology of the grains of the aluminum alloy 200a itself tends to be columnar crystals, which increases the yield strength of the aluminum alloy 200a, so that the yield strength of the aluminum alloy 200a reaches more than 150Mpa. In the process of heat treating the composite structure, the strength of the composite structure is further increased. After the aluminum alloy 200a and the titanium alloy 100 have sufficient connection strength, the installation groove is processed and set in the aluminum alloy 200a. After the terminal components are placed in the installation groove, the terminal components are protected by the terminal shell.

[0265] Embodiment 3

[0266] Figure 7 The flowchart of the shell manufacturing method in one embodiment of the present application is shown. The light metal material 200 in the shell is aluminum alloy 200a.

[0267] like Figure 7 As shown, the shell preparation method includes:

[0268] S100, preparing a composite structure by a composite structure preparation method.

[0269] S200, processing the composite structure to form a terminal housing.

[0270] The composite structure preparation method includes:

[0271] S110, bringing the surface of the titanium alloy 100 into contact with the molten aluminum alloy.

[0272] S120 , controlling the molten aluminum alloy to solidify to form a composite structure, wherein at least a portion of the molten aluminum alloy solidifies to form an intermediate layer 300 .

[0273] In step S110, the step of preparing the titanium alloy 100 is also included:

[0274] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm long and 84 mm wide, and the inner wall of the accommodating cavity 101 is 154 mm long and 80 mm wide, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0275] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0276] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten aluminum alloy in the accommodating cavity 101 in step S120 , the aluminum element diffuses and reacts with the titanium element.

[0277] In step S110, the step of preparing aluminum material is also included:

[0278] S1121, prepare 7075 aluminum alloy as aluminum material. The outer dimensions of the aluminum material are consistent with the dimensions of the accommodating cavity 101.

[0279] S1122, insert the aluminum material into the accommodating cavity 101, make the outer surface of the aluminum material contact the inner wall of the accommodating cavity 101 as much as possible, and discharge the gas between the outer surface of the aluminum material and the inner surface of the accommodating cavity 101.

[0280] On the one hand, 7075 aluminum alloy has high strength, and on the other hand, it is heat treatable and can further enhance its performance during subsequent heat treatment.

[0281] In step S110, the step of forming a molten aluminum alloy is also included:

[0282] S1131, heating the aluminum material so that a molten aluminum alloy is formed on the outer surface of the aluminum material. An induction coil is arranged outside the titanium alloy 100, and the induction coil is energized so that the outer surface of the aluminum material is heated and melted to form a molten aluminum alloy, and the molten aluminum alloy contacts the inner surface of the accommodating cavity 101, that is, the molten aluminum alloy contacts the surface of the titanium alloy 100. The temperature of the molten aluminum alloy is controlled at 730-750°C.

[0283] In step S120, it also includes:

[0284] S121, the molten aluminum alloy is kept warm for 10-30 minutes. The titanium element and the aluminum element in the intermediate layer 300 are diffused and combined through solid-liquid diffusion at the interface between the molten aluminum alloy and the titanium alloy 100.

[0285] S122, air-cooling the composite structure to room temperature, thereby controlling the structural composition of the middle layer 300 and ensuring the strength of the middle layer 300.

[0286] In step S121 , the temperature of the molten aluminum alloy is controlled so that the titanium element and the aluminum element can fully diffuse and combine, so that the intermediate layer 300 forms a reasonable element distribution.

[0287] The composite structure prepared by the above steps has similar metallographic characteristics to the composite structure in the first embodiment at the position of the intermediate layer 300 .

[0288] The molten aluminum alloy can also form a cast layer, which is formed by solidifying the molten aluminum alloy formed in step S1131. The aluminum alloy 200a in the cast layer has coarse grains, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the cast layer of the aluminum alloy 200a has higher strength. In addition, the connection strength between the aluminum alloy 200a and the intermediate layer 300 can be effectively improved.

[0289] The process of machining the composite structure to form the terminal housing includes:

[0290] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0291] S220, shaping and heat treating the composite structure to form a blank.

[0292] S230, processing a mounting groove in the blank.

[0293] S240, surface treating the blank to form a terminal housing.

[0294] In step S220, it includes:

[0295] S221, grinding of composite structures to remove burrs.

[0296] S222, solution heat treatment is performed on the composite structure. It includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is controlled between 500-550°C, and the solution time is controlled between 30-300mins. In this process, the strength of the aluminum alloy 200a can be further improved. In this process, the strength of the aluminum alloy 200a can be further improved. After the composite structure is heated to 500-550°C, it is kept warm for 30-50mins to obtain a composite structure with a certain improvement in the strength of the aluminum alloy 200a. Controlling the holding time to 30-50mins can save preparation time.

[0297] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0298] S224, aging heat treatment is performed on the composite structure. The composite structure is kept at 110-150°C for 6 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the aluminum alloy 200a.

[0299] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to aging heat treatment.

[0300] It is understandable that when the aluminum material is not 7075 aluminum alloy, the solution temperature can be adjusted. For example, when 6013 aluminum alloy or 6063 aluminum alloy is used, the solution temperature can be controlled at 490-540°C.

[0301] In step S230, it includes:

[0302] S231, through forging or full CNC machining, the blank is processed to process the installation groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the installation groove and the outer dimensions are more accurate.

[0303] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0304] In step S240, it includes:

[0305] S241, coating the surface of the blank with a film layer. The blank after nano injection molding is placed in a PVD device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0306] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0307] It is understandable that the mounting groove may not be completely formed on the aluminum alloy 200 a , and the mounting groove may be processed and set on both the titanium alloy 100 and the aluminum alloy 200 a .

[0308] It can be understood that in the above process, after the molten aluminum alloy is cooled and solidified by the crystallizer and the composite structure is cooled to room temperature, the intermediate layer 300 has appeared, and the yield strength of the aluminum alloy 200a has reached 150Mpa. The composite structure has met the preparation requirements of the terminal shell, and the composite structure is heated and quenched again in the subsequent step S220 to further strengthen the shear strength of the composite structure and increase the yield strength of the aluminum alloy 200a, which can further enhance the product quality of the terminal shell.

[0309] A method for preparing a shell by heating the outer surface of an aluminum material, comprising:

[0310] S1111, prepare titanium alloy 100 for the frame structure.

[0311] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0312] S1121, prepare 7075 aluminum alloy as the aluminum material.

[0313] S1122, insert the aluminum material into the accommodating cavity 101, make the outer surface of the aluminum material contact the inner wall of the accommodating cavity 101 as much as possible, and discharge the gas between the outer surface of the aluminum material and the inner surface of the accommodating cavity 101.

[0314] S1131, heating the aluminum material so that a molten aluminum alloy is formed on the outer surface of the aluminum material. The temperature of the molten aluminum alloy is controlled to be 690-750°C.

[0315] S121, keep the molten aluminum alloy warm for 10-30 minutes.

[0316] S122, air-cooling the composite structure to room temperature.

[0317] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0318] S221, grinding of composite structures to remove burrs.

[0319] S222, heating the composite structure, keeping the temperature, and then quenching to room temperature. The composite structure is heated to between 500-550°C, kept at the temperature for 30-300 minutes, and then quenched to room temperature.

[0320] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0321] S224, aging heat treatment of the composite structure. The composite structure is kept at 110-150°C for 6 hours.

[0322] S230, processing the installation groove and the outer dimensions on the blank.

[0323] S241, nano-injection molding the inner wall of the installation groove.

[0324] S242, coating the surface of the blank with a film layer.

[0325] It is understandable that other conventional methods may be used to heat the aluminum material so that the outer surface of the aluminum material melts to form a molten aluminum alloy.

[0326] It can be understood that the lightweight metal material 200 can not only be aluminum alloy 200a, but can also be replaced by an aluminum-based composite material obtained by adding a reinforcing phase to an aluminum alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0327] Through this shell preparation method, the molten aluminum alloy has a sufficiently long solidification time, and the intermediate layer 300 between the aluminum alloy 200a and the titanium alloy 100 has sufficient shear strength. In the process of heat treating the composite structure, the strength of the composite structure is further increased. After the aluminum alloy 200a and the titanium alloy 100 have sufficient connection strength, the aluminum alloy 200a is processed to set a mounting groove, and after the terminal components are placed in the mounting groove, the terminal shell provides protection for the terminal components.

[0328] Embodiment 4

[0329] Figure 8 A flow chart of a method for preparing a shell in one embodiment of the present application is shown, wherein the lightweight metal material in the shell is magnesium alloy 200b.

[0330] like Figure 8 As shown, the shell preparation method includes:

[0331] S100, preparing a composite structure by a composite structure preparation method.

[0332] S200, processing the composite structure to form a terminal housing.

[0333] The composite structure preparation method includes:

[0334] S110, bringing the surface of the titanium alloy 100 into contact with the molten magnesium alloy.

[0335] S120 , maintaining surface contact between the molten magnesium alloy and the titanium alloy 100 , and forming the intermediate layer 300 through solid-liquid diffusion at the interface between the molten magnesium alloy and the titanium alloy 100 .

[0336] In step S110, the step of preparing the titanium alloy 100 is also included:

[0337] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer circumference of the titanium alloy 100 is 155 mm and the width is 85 mm. The inner wall of the accommodating cavity 101 is 149 mm long and 79 mm wide, that is, the wall thickness of the titanium alloy 100 is 0.5 mm. The size of the titanium alloy 100 in the first direction X is 200 mm.

[0338] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0339] S1113, partially placing the titanium alloy 100 in the crystallizer. The first direction X is a vertical direction, an end of the titanium alloy 100 facing away from the opening is located in the crystallizer, and the opening of the titanium alloy 100 is located above the crystallizer.

[0340] The size of the accommodating cavity 101 reaches 149×79 mm, which increases the amount of molten magnesium alloy stored in the accommodating cavity 101, thereby slowing down the solidification process of the molten magnesium alloy in the accommodating cavity 101, extending the solidification time of the molten magnesium alloy, allowing sufficient solid-liquid diffusion and reaction at the titanium-magnesium interface, and improving the titanium-magnesium bonding strength.

[0341] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten magnesium alloy in the accommodating cavity 101 in step S120 , the magnesium element diffuses and reacts with the titanium element.

[0342] The cooperation between the crystallizer and the titanium alloy 100 prepares for the subsequent solidification of the molten magnesium alloy.

[0343] In step S110, the step of preparing a molten magnesium alloy is also included:

[0344] S1121, preparing AZ91D magnesium alloy as a magnesium material, and melting the magnesium material under an inert atmosphere to form a molten magnesium alloy.

[0345] On the one hand, AZ91D magnesium alloy has high strength, and on the other hand, it is heat treatable and can further enhance its performance during subsequent heat treatment.

[0346] In step S110, the step of controlling the initial temperature of the molten magnesium alloy is also included:

[0347] S1131, controlling the atmosphere when the molten magnesium alloy is injected into the receiving cavity 101 to be an inert atmosphere.

[0348] S1132, controlling the temperature of the molten magnesium alloy injected into the receiving cavity 101 to be between 680°C and 730°C.

[0349] Corresponding to the above-mentioned size of the containing cavity 101, the temperature of the molten magnesium alloy is controlled to be in the range of 680-730°C, which can effectively control the yield strength of the final magnesium alloy 200b to be above 150 MPa.

[0350] In step S120, it also includes:

[0351] S121, keep the accommodating chamber 101 in an inert atmosphere, and draw the titanium alloy 100 to move in the crystallizer, so that the accommodating chamber 101 gradually passes through the crystallizer from the end away from the opening to the end close to the opening. Control the speed of drawing the titanium alloy 100 so that the solidification time of each local molten magnesium alloy in the titanium alloy 100 is between 8-10 minutes. Through the solid-liquid diffusion at the interface of the molten magnesium alloy and the titanium alloy 100, the diffusion and combination of the titanium element and the magnesium element in the intermediate layer 300 are achieved.

[0352] S122, after the overall temperature of the composite structure is reduced to between 390-460°C, the composite structure is water-cooled to room temperature, thereby controlling the structural composition of the middle layer 300 and ensuring the strength of the middle layer 300. Before water cooling, the overall temperature of the composite structure is determined according to the temperature of the molten aluminum alloy when it is injected into the accommodating cavity 101.

[0353] In step S121, the solidification speed of the molten magnesium alloy is controlled by the drawing speed, which can effectively ensure the yield strength of the magnesium alloy after solidification, and at the same time, the titanium element and the magnesium element can be fully diffused and combined, so that the intermediate layer 300 forms a reasonable element distribution.

[0354] In step S122 , the grain size of the magnesium alloy 200 b is controlled by water cooling, and the structural composition of the intermediate layer 300 is controlled to ensure the strength of the intermediate layer 300 .

[0355] After all the molten magnesium alloy solidifies, the whole magnesium alloy 200b is formed. The whole magnesium alloy 200b is a cast layer showing a cast structure. The magnesium alloy 200b with a cast structure has coarse grains, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the magnesium alloy 200b has a higher strength. In addition, the cast structure has a higher connection strength with the intermediate layer 300.

[0356] The composite structure prepared by the above steps has similar metallographic characteristics to the composite structure in Example 1.

[0357] The interface shear strength of the intermediate layer 300 reaches 65 MPa. The interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥ 60 MPa, and the interface shear strength between the intermediate layer 300 and the magnesium alloy 200b is ≥ 60 MPa. The yield strength of the magnesium alloy 200b reaches 120 MPa, and the elongation reaches 8%. The hardness of the titanium alloy 100 reaches 350 Hv.

[0358] The process of machining the composite structure to form the terminal housing includes:

[0359] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0360] S220, shaping and heat treating the composite structure to form a blank.

[0361] S230, processing the installation groove and the outer dimensions on the blank.

[0362] S240, surface treating the blank to form a terminal housing.

[0363] In step S210, the preset size can be adjusted according to the terminal shell. For example, the preset size is 1-2 mm larger than the final size of the terminal shell. In the first direction X, the size of the finished terminal shell is 8 mm, and the size loss caused by further cutting, shaping and compression of the composite structure in subsequent processing can be considered, and the preset size can be set to 9-10 mm.

[0364] In step S220, it includes:

[0365] S221, grinding of composite structures to remove burrs.

[0366] S222, solution heat treatment is performed on the composite structure. It includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is controlled between 390-460°C, and the solution time is controlled between 30-300 minutes. In this process, the strength of magnesium alloy 200b can be further improved. After the composite structure is heated to 390-460°C, it is kept warm for 30-50 minutes to obtain a composite structure with a certain improvement in the strength of magnesium alloy 200b. Controlling the solution time to 30-50 minutes can save preparation time.

[0367] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0368] S224, performing aging heat treatment on the composite structure. Specifically, the composite structure is kept at 140-180°C for 4-10 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the magnesium alloy 200b.

[0369] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to heat treatment.

[0370] After the processing of step S220, the interface shear strength of the composite structure can be further improved to 85Mpa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥80Mpa, and the interface shear strength between the intermediate layer 300 and the magnesium alloy 200b is ≥80Mpa. The yield strength of the magnesium alloy 200b can be further improved to 160Mpa, and the elongation of the magnesium alloy 200b reaches 5%. The hardness of the titanium alloy 100 reaches 320Hv.

[0371] The shear test of the composite structure before step S220 is compared with the shear test of the composite structure after step S220. The shear ports of both are not in the middle layer 300, but are located at the position of the magnesium alloy 200b close to the middle layer 300. Therefore, the improvement of the interface shear strength in step S220 is caused by the improvement of the yield strength of the magnesium alloy 200b, which ensures the overall strength of the composite structure.

[0372] In step S230, it includes:

[0373] S231, through forging or full CNC machining, the blank is processed to process the installation groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the installation groove and the outer dimensions are more accurate.

[0374] The mounting slot is designed according to the terminal components that are actually required to be installed in the terminal housing, and the external dimensions are determined according to the appearance design of the actual terminal housing.

[0375] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0376] In step S240, it includes:

[0377] S241, coating the surface of the blank with a film layer. The blank after nano injection molding is placed in a PVD device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0378] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0379] It is understandable that the mounting groove may not be completely formed on the magnesium alloy 200 b , and the mounting groove may be processed and set on both the titanium alloy 100 and the magnesium alloy 200 b .

[0380] Fig. 9 A schematic structural diagram of a composite structure in one embodiment of the present application is shown.

[0381] A method for preparing a shell by using a crystallizer to assist the solidification of a molten magnesium alloy, comprising:

[0382] S1111, prepare a square tube of titanium alloy 100. Fig. 9 As shown, in the cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 155 mm long and 85 mm wide, and the inner wall of the accommodating cavity 101 is 149 mm long and 79 mm wide, that is, the wall thickness of the titanium alloy 100 is 3 mm. The dimension of the titanium alloy 100 in the first direction X is 200 mm.

[0383] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0384] S1113, partially placing the titanium alloy 100 in the crystallizer. The first direction X is a vertical direction, an end of the titanium alloy 100 facing away from the opening is located in the crystallizer, and the opening of the titanium alloy 100 is located above the crystallizer.

[0385] S1121, preparing AZ91D magnesium alloy as a magnesium material, melting the magnesium material, and forming a molten magnesium alloy.

[0386] S1131, controlling the atmosphere when the molten magnesium alloy is injected into the receiving cavity 101 to be an inert atmosphere.

[0387] S1132, injecting the molten magnesium alloy into the containing cavity 101 from the opening, and controlling the temperature of the molten magnesium alloy injected into the containing cavity 101 to be 680-730°C.

[0388] S121, the accommodating chamber 101 is kept in an inert atmosphere, and the titanium alloy 100 is stretched and moved in the crystallizer, so that the accommodating chamber 101 gradually passes through the crystallizer from the end away from the opening to the end close to the opening. The speed of stretching the titanium alloy 100 is controlled so that the solidification time of each local molten magnesium alloy in the titanium alloy 100 is between 8 and 10 minutes.

[0389] S122, after the overall temperature of the composite structure is reduced to below 390-460°C, the composite structure is water-cooled to room temperature.

[0390] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0391] S221, grinding of composite structures to remove burrs.

[0392] S222, heating the composite structure, keeping the temperature, and then quenching to room temperature. The composite structure is heated to between 390-460°C, kept at the temperature for 30-50 minutes, and then quenched to room temperature.

[0393] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0394] S224, aging heat treatment of the composite structure. The composite structure is kept at 140-180°C for 4-10 hours.

[0395] S231, through forging or full CNC machining, the blank is processed to have the mounting groove and external dimensions.

[0396] S232, nano-injection molding the inner wall of the installation groove.

[0397] S240, coating the surface of the blank with a film layer.

[0398] It can be understood that the lightweight metal material 200 can not only be a magnesium alloy 200b, but can also be replaced by a magnesium-based composite material obtained by adding a reinforcing phase to a magnesium alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0399] The terminal shell prepared by this shell preparation method combines titanium alloy and magnesium alloy through the intermediate layer, so that the connection strength of magnesium alloy and titanium alloy is relatively high. The composition changes of the first transition layer, the stabilization layer and the second transition layer are stable, which can improve the interface shear strength between the intermediate layer and the titanium alloy, improve the interface shear strength between the intermediate layer and the magnesium alloy, and improve the strength of the intermediate layer itself. Thereby, the overall strength of the terminal shell is improved.

[0400] Embodiment 5

[0401] Fig.10 The flowchart of the shell manufacturing method in one embodiment of the present application is shown. The light metal material in the shell is magnesium alloy 200b.

[0402] like Fig.10 As shown, the shell preparation method includes:

[0403] S100, preparing a composite structure by a composite structure preparation method.

[0404] S200, processing the composite structure to form a terminal housing.

[0405] The composite structure preparation method includes:

[0406] S110, bringing the surface of the titanium alloy 100 into contact with the molten magnesium alloy.

[0407] S120, maintaining surface contact between the molten magnesium alloy and the titanium alloy 100, forming an intermediate layer 300 through solid-liquid diffusion at the interface of the molten magnesium alloy and the titanium alloy 100, controlling the solidification of the molten magnesium water to form a composite structure, and at least a portion of the molten magnesium water solidifies to form the intermediate layer 300.

[0408] In step S110, the step of preparing the titanium alloy 100 is also included:

[0409] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm long and 84 mm wide, and the inner wall of the accommodating cavity 101 is 154 mm long and 80 mm wide, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0410] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0411] S1113, placing the titanium alloy 100 in a die-casting mold. The first direction X is a horizontal direction, and the molten magnesium alloy is injected into the titanium alloy 100 in a horizontal direction by an injection device under an inert atmosphere. The inert atmosphere can be a nitrogen atmosphere, an argon atmosphere, etc. The inert atmosphere can reduce the oxidation probability of the magnesium alloy.

[0412] The size of the accommodating cavity 101 reaches 160×84 mm, which increases the amount of molten magnesium alloy stored in the accommodating cavity 101, thereby slowing down the solidification process of the molten magnesium alloy in the accommodating cavity 101 and extending the solidification time of the molten magnesium alloy, so that the magnesium alloy 200b has sufficient strength.

[0413] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten magnesium alloy in the accommodating cavity 101 in step S120 , the magnesium element diffuses and reacts with the titanium element.

[0414] The titanium alloy 100 is placed in a die-casting mold to prepare for the subsequent solidification of the molten magnesium alloy.

[0415] In step S110, the step of preparing a molten magnesium alloy is also included:

[0416] S1121, preparing AM60B magnesium alloy as a magnesium material, placing the magnesium material in a heating container, and melting the magnesium material under an inert atmosphere to form a molten magnesium alloy.

[0417] AM60B magnesium alloy has high strength on the one hand and heat treatability on the other hand, which can further enhance its performance during subsequent heat treatment.

[0418] During the process of injecting the molten magnesium alloy into the titanium alloy 100, the channel at the bottom of the heating container is opened, and the molten magnesium alloy enters the titanium alloy 100 from the bottom of the heating container. During the process of injecting the molten magnesium alloy into the titanium alloy 100, the molten magnesium alloy is protected by an inert atmosphere, which effectively reduces the probability of oxidation of the molten magnesium alloy.

[0419] In step S110, the step of controlling the initial temperature of the molten magnesium alloy is also included:

[0420] S1131, controlling the temperature of the molten magnesium alloy injected into the accommodating cavity 101 to be between 680°C and 730°C. Controlling the temperature of the die-casting mold to be between 250°C and 300°C.

[0421] In step S120, it also includes:

[0422] S121, the portion of the molten magnesium alloy near the titanium alloy 100 solidifies in the titanium alloy 100 for more than 1 minute, and then cools to 400° C. The titanium element and the magnesium element in the intermediate layer 300 diffuse and combine through solid-liquid diffusion at the interface of the molten aluminum alloy and the titanium alloy 100.

[0423] S122, after the overall temperature of the composite structure is reduced to between 420-480°C, the composite structure is placed in an inert atmosphere and cooled to room temperature, thereby controlling the structural composition of the intermediate layer 300 and ensuring the strength of the intermediate layer 300.

[0424] Controlling the temperature of the die casting mold in step S121 can control the solidification rate of the molten magnesium alloy, effectively ensuring the yield strength of the solidified magnesium alloy 200b, and at the same time allowing the titanium element and the magnesium element to fully diffuse and combine, so that the intermediate layer 300 forms a reasonable element distribution.

[0425] In step S122 , the grain size of the magnesium alloy 200 b is controlled by cooling in an inert atmosphere, and the structural composition of the intermediate layer 300 is controlled to ensure the strength of the intermediate layer 300 .

[0426] The entire solidification process of the molten magnesium alloy is completed under an inert atmosphere. After all the molten magnesium alloys solidify, a whole magnesium alloy 200b is formed. The entire magnesium alloy 200b is a cast layer showing a cast structure. The magnesium alloy 200b with a cast structure has coarse grains, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the magnesium alloy 200b has a higher strength. Moreover, the cast structure has a higher connection strength with the intermediate layer 300.

[0427] The composite structure prepared by the above steps has similar metallographic characteristics to the composite structure in Example 1.

[0428] The composite structure prepared by the above steps has an interface shear strength of 55 MPa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥55 MPa, and the interface shear strength between the intermediate layer 300 and the magnesium alloy 200b is ≥55 MPa. The yield strength of the magnesium alloy 200b reaches 130 MPa, the elongation reaches 5%, and the hardness of the titanium alloy 100 reaches 450 Hv.

[0429] The process of machining the composite structure to form the terminal housing includes:

[0430] S210, cutting the composite structure. Removing the protruding features such as the material head formed when the composite structure is die-cast.

[0431] S220, shaping and heat treating the composite structure to form a blank.

[0432] S230, processing the installation groove and the outer dimensions on the blank.

[0433] S240, surface treating the blank to form a terminal housing.

[0434] In step S220, it includes:

[0435] S222, solution heat treatment is performed on the composite structure. It includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is controlled between 390-460°C, and the solution time is controlled between 30-300 minutes. In this process, the strength of magnesium alloy 200b can be further improved. After the composite structure is heated to 390-460°C, it is kept warm for 30-50 minutes to obtain a composite structure with a certain improvement in the strength of magnesium alloy 200b. Controlling the solution time to 30-50 minutes can save preparation time.

[0436] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0437] S224, performing aging heat treatment on the composite structure. Specifically, the composite structure is kept at 140-180°C for 4-10 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the magnesium alloy 200b.

[0438] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to aging heat treatment.

[0439] It is understandable that when the composite structure itself has sufficient strength and the composite structure generated by the die-casting process is basically consistent with the external dimensions of the terminal housing, the composite structure can be simply shaped by grinding and removing burrs. Neither solution heat treatment nor large-scale shaping is performed. After the composite structure is simply shaped, the composite structure can be subjected to aging heat treatment to adjust the performance of the composite structure.

[0440] After the processing of step S220, the composite structure is shaped without solution heat treatment, and the temperature in the aging heat treatment is controlled between 155-165°C and kept warm for 5 hours. The interface shear strength of the composite structure can be further increased to 70Mpa. That is, the interface shear strength between the intermediate layer 300 and the titanium alloy 100 is ≥70Mpa, and the interface shear strength between the intermediate layer 300 and the magnesium alloy 200b is ≥70Mpa. The yield strength of the magnesium alloy 200b can be further increased to 160Mpa, and the elongation of the magnesium alloy 200b reaches 3%. The hardness of the titanium alloy 100 reaches 420Hv.

[0441] In step S230, the blank is processed by forging or full CNC machining to form the installation groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the installation groove, and the outer dimensions are more accurate. The installation groove is formed by CNC machining to improve the accuracy of the installation groove.

[0442] The mounting slot is designed according to the terminal components that are actually required to be installed in the terminal housing, and the external dimensions are determined according to the appearance design of the actual terminal housing.

[0443] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0444] In step S240, it includes:

[0445] S241, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0446] S242S241, coating the surface of the blank. The blank after nano injection molding is placed in a PVD device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0447] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0448] It is understandable that the mounting groove may not be completely formed on the magnesium alloy 200 b , and the mounting groove may be processed and set on both the titanium alloy 100 and the magnesium alloy 200 b .

[0449] It can be understood that in the above process, after the molten magnesium alloy is cooled and solidified by the crystallizer and the composite structure is cooled to room temperature, the intermediate layer 300 has appeared, and the yield strength of the magnesium alloy 200b has reached 150Mpa. The composite structure has met the preparation requirements of the terminal shell. In the subsequent step S220, the composite structure is heated and quenched again to further strengthen the shear strength of the composite structure and increase the yield strength of the magnesium alloy 200b, which can further enhance the product quality of the terminal shell.

[0450] It is understandable that in addition to AM60B magnesium alloy as the magnesium material, other magnesium alloys such as AZ91D can also be used as the magnesium material.

[0451] A method for preparing a shell by using a die-casting mold to assist the solidification of a molten magnesium alloy, comprising:

[0452] S1111, prepare a square titanium alloy 100, in the cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm, the width is 84 mm, the inner wall of the accommodating cavity 101 is 154 mm long, and the width is 80 mm, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0453] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0454] S1113, placing the titanium alloy 100 in a die-casting mold. The first direction X is a horizontal direction, and the molten magnesium alloy is injected into the titanium alloy 100 along the horizontal direction by an injection device.

[0455] S1121, preparing AM60B magnesium alloy as a magnesium material, and melting the magnesium material to form a molten magnesium alloy.

[0456] S1131, controlling the temperature of the molten magnesium alloy injected into the accommodating cavity 101 to be between 680°C and 730°C. Controlling the temperature of the die-casting mold to be between 250°C and 300°C.

[0457] S121, the molten magnesium alloy is solidified in the titanium alloy 100 for more than 1 minute and then cooled to 400°C.

[0458] S122, after the overall temperature of the composite structure is reduced to between 420-480°C, the composite structure is air-cooled to room temperature.

[0459] S210, cutting the composite structure. Removing the protruding features such as the material head formed when the composite structure is die-cast.

[0460] S221, grinding of composite structures to remove burrs.

[0461] S222, performing solution heat treatment on the composite structure.

[0462] S223, shaping the composite structure.

[0463] S224, performing aging heat treatment on the composite structure.

[0464] S231, processing the installation groove and the outer dimensions on the blank.

[0465] S232, nano-injection molding the inner wall of the installation groove.

[0466] S241, coating the surface of the blank with a film layer.

[0467] It can be understood that the lightweight metal material 200 can not only be a magnesium alloy 200b, but can also be replaced by a magnesium-based composite material obtained by adding a reinforcing phase to a magnesium alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0468] Through this shell preparation method, the molten magnesium alloy has a sufficiently long solidification time, and the intermediate layer 300 between the magnesium alloy 200b and the titanium alloy 100 has sufficient shear strength. The growth morphology of the grains of the magnesium alloy 200b itself tends to be columnar crystals, which increases the yield strength of the magnesium alloy 200b, so that the yield strength of the magnesium alloy 200b reaches more than 150Mpa. In the process of heat treating the composite structure, the strength of the composite structure is further increased. After the magnesium alloy 200b and the titanium alloy 100 have sufficient connection strength, the magnesium alloy 200b is processed to set the installation groove. After the terminal components are placed in the installation groove, the terminal components are protected by the terminal shell.

[0469] Embodiment 6

[0470] Fig.11 The flowchart of the shell manufacturing method in one embodiment of the present application is shown. The light metal material in the shell is magnesium alloy 200b.

[0471] like Fig.11 As shown, the shell preparation method includes:

[0472] S100, preparing a composite structure by a composite structure preparation method.

[0473] S200, processing the composite structure to form a terminal housing.

[0474] The composite structure preparation method includes:

[0475] S110, bringing the surface of the titanium alloy 100 into contact with the molten magnesium alloy.

[0476] S120 , controlling the molten magnesium alloy to solidify to form a composite structure, wherein at least a portion of the molten magnesium alloy solidifies to form an intermediate layer 300 .

[0477] In step S110, the step of preparing the titanium alloy 100 is also included:

[0478] S1111, prepare a titanium alloy 100 of a frame structure. The titanium alloy 100 is roughly in the shape of a square tube. In a cross section perpendicular to the first direction X, the outer perimeter of the titanium alloy 100 is 160 mm long and 84 mm wide, and the inner wall of the accommodating cavity 101 is 154 mm long and 80 mm wide, that is, the wall thickness of the titanium alloy 100 is 2 mm. The size of the titanium alloy 100 in the first direction X is 9 mm.

[0479] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0480] The inner wall surface of the accommodating cavity 101 is made neat by grinding and cleaning, so that during the solidification process of the molten magnesium alloy in the accommodating cavity 101 in step S120 , the magnesium element diffuses and reacts with the titanium element.

[0481] In step S110, the step of preparing magnesium material is also included:

[0482] S1121, prepare AZ91D magnesium alloy as magnesium material. The outer dimensions of the magnesium material are consistent with the dimensions of the accommodating cavity 101.

[0483] S1122, inserting the magnesium material into the accommodating chamber 101, making the outer surface of the magnesium material contact the inner wall of the accommodating chamber 101 as much as possible, and exhausting the gas between the outer surface of the magnesium material and the inner surface of the accommodating chamber 101.

[0484] On the one hand, AZ91D magnesium alloy has high strength, and on the other hand, it is heat treatable and can further enhance its performance during subsequent heat treatment.

[0485] In step S110, the step of forming a molten magnesium alloy is also included:

[0486] S1131, heat the magnesium material so that a molten magnesium alloy is formed on the outer surface of the magnesium material. An induction coil is arranged outside the titanium alloy 100, and the induction coil is energized so that the outer surface of the magnesium material is heated and melted to form a molten magnesium alloy, and the molten magnesium alloy contacts the inner surface of the accommodating cavity 101, that is, the molten magnesium alloy contacts the surface of the titanium alloy 100. The temperature of the molten magnesium alloy is controlled at 680-730°C.

[0487] In step S120, it also includes:

[0488] S121, the molten magnesium alloy is kept warm for 10-30 minutes. The titanium element and the magnesium element in the intermediate layer 300 are diffused and combined through solid-liquid diffusion at the interface of the molten aluminum alloy and the titanium alloy 100.

[0489] S122, air-cooling the composite structure to room temperature, thereby controlling the structural composition of the middle layer 300 and ensuring the strength of the middle layer 300.

[0490] In step S121 , the temperature of the molten magnesium alloy is controlled so that the titanium element and the magnesium element can be fully diffused and combined, so that the intermediate layer 300 forms a reasonable element distribution.

[0491] The composite structure prepared by the above steps has similar metallographic characteristics to the composite structure in the first embodiment at the position of the intermediate layer 300 .

[0492] The molten magnesium alloy can also form a cast layer, which is formed by solidifying the molten magnesium alloy formed in step S1131. The magnesium alloy 200b has coarse grains in the cast layer, and can also have obvious grain boundaries or intracrystalline segregation, columnar crystals or dendritic crystals, so that the cast layer of the magnesium alloy 200b has higher strength. And the connection strength between the magnesium alloy 200b and the intermediate layer 300 can be effectively improved.

[0493] The process of machining the composite structure to form the terminal housing includes:

[0494] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0495] S220, shaping and heat treating the composite structure to form a blank.

[0496] S230, processing a mounting groove in the blank.

[0497] S240, surface treating the blank to form a terminal housing.

[0498] In step S220, it includes:

[0499] S221, grinding of composite structures to remove burrs.

[0500] S222, solution heat treatment is performed on the composite structure. This includes heating the composite structure to the solution temperature, keeping the temperature for the solution time, and then quenching to room temperature. The solution temperature is controlled between 390-460°C, and the solution time is controlled between 30-300 minutes. In this process, the strength of magnesium alloy 200b can be further improved. If the preparation time needs to be shortened, the composite structure can be kept at 390-460°C for 30-50 minutes and then quenched to room temperature.

[0501] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0502] S224, aging heat treatment is performed on the composite structure. The composite structure is kept at 140-180°C for 4-10 hours. On the one hand, this aging heat treatment in the form of annealing can reduce the internal stress generated during the shaping process of the composite structure. On the other hand, it can also further increase the yield strength of the magnesium alloy 200b.

[0503] It is understandable that when the composite structure itself has sufficient strength, the composite structure may not be subjected to solution heat treatment, but only the composite structure may be shaped and then subjected to aging heat treatment.

[0504] In step S230, it includes:

[0505] S231, through forging or full CNC machining, the blank is processed to process the installation groove and the outer dimensions. Forging or full CNC machining can improve the accuracy of the installation groove and the outer dimensions are more accurate.

[0506] S232, nano-injection molding is performed on the inner wall of the installation groove to form a high-precision insulation layer inside the installation groove to improve the connection strength between the plastic and metal parts.

[0507] In step S240, it includes:

[0508] S241, coating the surface of the blank with a film layer. The blank after nano injection molding is placed in a PVD device for coating, so that the terminal shell has a colored appearance. At the same time, the corrosion resistance of the terminal shell can also be increased.

[0509] It is understandable that in step S240, the surface of the blank may be treated by polishing, sandblasting, brushing or other methods, so that the terminal housing has an appearance with good visual effect.

[0510] It is understandable that the mounting groove may not be completely formed on the magnesium alloy 200 b , and the mounting groove may be processed and set on both the titanium alloy 100 and the magnesium alloy 200 b .

[0511] It can be understood that in the above process, after the molten magnesium alloy is cooled and solidified by the crystallizer and the composite structure is cooled to room temperature, the intermediate layer 300 has appeared, and the yield strength of the magnesium alloy 200b has reached 150Mpa. The composite structure has met the preparation requirements of the terminal shell. In the subsequent step S220, the composite structure is heated and quenched again to further strengthen the shear strength of the composite structure and increase the yield strength of the magnesium alloy 200b, which can further enhance the product quality of the terminal shell.

[0512] A method for preparing a shell by heating the outer surface of a magnesium material, comprising:

[0513] S1111, prepare titanium alloy 100 for the frame structure.

[0514] S1112, grinding and cleaning the inner wall surface of the accommodating cavity 101 of the titanium alloy 100.

[0515] S1121, prepare AZ91D magnesium alloy as a magnesium material.

[0516] S1122, inserting the magnesium material into the accommodating chamber 101, making the outer surface of the magnesium material contact the inner wall of the accommodating chamber 101 as much as possible, and exhausting the gas between the outer surface of the magnesium material and the inner surface of the accommodating chamber 101.

[0517] S1131, heating the magnesium material so that a molten magnesium alloy is formed on the outer surface of the magnesium material. The temperature of the molten magnesium alloy is controlled to be 690-750°C.

[0518] S121, keep the molten magnesium alloy warm for 10-30 minutes.

[0519] S122, air-cooling the composite structure to room temperature.

[0520] S210, cutting the composite structure so that a size of the composite structure in a first direction X reaches a preset size corresponding to the terminal housing.

[0521] S221, grinding of composite structures to remove burrs.

[0522] S222, heating the composite structure, keeping the temperature, and then quenching to room temperature. The composite structure is heated to between 390-460°C, kept at the temperature for 30-300 minutes, and then quenched to room temperature. In this process, the strength of the magnesium alloy 200b can be further improved.

[0523] S223, shaping the composite structure. Eliminate the deformation of the composite structure during quenching. The flatness of the composite structure after leveling can be controlled within 0.3mm.

[0524] S224, aging heat treatment of the composite structure. The composite structure is kept at 140-180°C for 4-10 hours.

[0525] S230, processing the installation groove and the outer dimensions on the blank.

[0526] S241, nano-injection molding the inner wall of the installation groove.

[0527] S242, coating the surface of the blank with a film layer.

[0528] It is understandable that other conventional methods may be used to heat the magnesium material so that the outer surface of the magnesium material melts to form a molten magnesium alloy.

[0529] It can be understood that the lightweight metal material 200 can not only be a magnesium alloy 200b, but can also be replaced by a magnesium-based composite material obtained by adding a reinforcing phase to a magnesium alloy as a matrix; this replacement will not have a substantial impact on the solid-liquid diffusion, bonding principle, interface strength, interface stability and composite structure of the composite structure interface, and the production process of the composite structure to prepare the shell.

[0530] Through this shell preparation method, the molten magnesium alloy has a sufficiently long solidification time, and the intermediate layer 300 between the magnesium alloy 200b and the titanium alloy 100 has sufficient shear strength. In the process of heat treating the composite structure, the strength of the composite structure is further increased. After the magnesium alloy 200b and the titanium alloy 100 have sufficient connection strength, the magnesium alloy 200b is processed to set a mounting groove, and after the terminal components are placed in the mounting groove, the terminal components are protected by the terminal shell.

[0531] The above description is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present application should be included in the disclosure scope of the present application.

Claims

1. A composite structure, characterized in that: It comprises a titanium alloy, a light metal material and an intermediate layer; the intermediate layer is formed between the titanium alloy and the light metal material; The lightweight metal material includes an aluminum metal material or a magnesium metal material; From close to the lightweight metal material to close to the titanium alloy, the intermediate layer includes a first transition layer, a stabilization layer, and a second transition layer in sequence; In the first transition layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the first transition layer is |K L-1 |>30% / μm; In the second transition layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the second transition layer is |K L-2 |>45% / μm; In the stabilization layer, the mass fraction of the light metal element decreases from the side close to the light metal material to the side close to the titanium alloy, and the average change rate of the mass fraction of the light metal element in the stabilization layer is |K L-w |<15% / μm; The light metal element is the metal element with the highest content in the light metal material; The lightweight metal material comprises a cast layer showing a cast structure, and the cast layer is connected to the first transition layer.

2. The composite structure according to claim 1, characterized in that At least one of the first transition layer, the stabilization layer and the second transition layer has a size of 0.1-3 μm.

3. The composite structure according to claim 1, characterized in that One side of the intermediate layer is directly connected to the lightweight metal material, and the other side is directly connected to the titanium alloy. The interface shear strength between the intermediate layer and the titanium alloy is ≥55Mpa, and the interface shear strength between the intermediate layer and the lightweight metal material is ≥55Mpa.

4. The composite structure according to claim 1, characterized in that: The mass fraction ratio of the light metal element to the titanium element in the first transition layer is greater than 1; The mass fraction ratio of the light metal element to the titanium element in the second transition layer is less than 1.

5. The composite structure according to claim 1, characterized in that The lightweight metal material includes any one of 2 series aluminum alloy, 4 series aluminum alloy, 6 series aluminum alloy, 7 series aluminum alloy, die-cast aluminum alloy and die-cast magnesium alloy.

6. The composite structure according to claim 1, characterized in that: The titanium alloy is a frame structure having a containing cavity; The light metal material is disposed in the accommodating cavity.

7. A terminal housing, characterized in that: A composite structure comprising any one of claims 1 to 6; The composite structure is provided with a mounting groove, and the mounting groove is used for placing terminal components.

8. The terminal housing according to claim 7, characterized in that: The titanium alloy is a frame structure having a containing cavity; The light metal material is disposed in the accommodating cavity; The lightweight metal material is provided with the mounting groove.

9. A method for preparing a composite structure, characterized in that: For preparing a composite structure as claimed in any one of claims 1 to 5, comprising: contacting the surface of the titanium alloy with a molten light metal material; The surfaces of the molten light metal material and the titanium alloy are kept in contact, and the intermediate layer is formed through solid-liquid diffusion at the interface between the molten light metal material and the titanium alloy.

10. The method for preparing a composite structure according to claim 9, characterized in that: The step of contacting the surface of the titanium alloy with a molten light metal material comprises: Providing a light metal material substrate and a titanium alloy substrate, and placing the light metal material substrate close to the titanium alloy substrate; The light metal material substrate is heated to form the molten light metal material in the contact interface region between the light metal material substrate and the titanium alloy substrate.

11. The method for preparing a composite structure according to claim 9, characterized in that ; The step of contacting the surface of the titanium alloy with a molten light metal material comprises: The titanium alloy is a frame structure having a containing cavity; The molten light metal material is injected into the accommodating cavity.

12. The method for preparing a composite structure according to claim 11, characterized in that: Before the step of injecting the molten light metal material into the accommodating cavity, the method includes: placing the titanium alloy part in a crystallizer; The step of injecting the molten light metal material into the accommodating cavity includes: the accommodating cavity has an opening, and the molten light metal material is injected into the accommodating cavity from the opening; The step of maintaining the surface contact between the molten light metal material and the titanium alloy includes: stretching the titanium alloy to move in the crystallizer so that the accommodating cavity gradually passes through the crystallizer from one end away from the opening to the end close to the opening.

13. The method for preparing a composite structure according to claim 11, characterized in that: Before the step of injecting the molten light metal material into the accommodating cavity, the method includes placing the titanium alloy in a die-casting mold.

14. A method for preparing a shell, characterized in that: The terminal housing is prepared by using the composite structure prepared by the composite structure preparation method according to any one of claims 9 to 13, further comprising: heat treating and shaping the composite structure to form a blank; Processing the blank to form a mounting groove and an outer dimension; The blank is surface treated to form the terminal housing.

15. The method for preparing a shell as claimed in claim 14, characterized in that: The titanium alloy is a frame structure having a receiving cavity, the lightweight metal material is located in the receiving cavity, and the receiving cavity extends along a first direction; Before the step of processing the blank into the installation groove and the outer dimensions, the step further includes: cutting the composite structure or the blank so that the size of the composite structure or the blank in the first direction after cutting reaches a preset size corresponding to the terminal shell.

16. The method for preparing a shell according to claim 14, characterized in that: The step of heat treating and shaping the composite structure to form a blank comprises: heating the composite structure to a solution temperature, and maintaining the temperature at the solution temperature for a solution time; The solution temperature is 490-540°C, or 500-550°C, or 480-540°C, or 390-460°C; The solution time is 30-300 min.

17. The method for preparing a shell according to claim 14, characterized in that: The step of heat treating and shaping the composite structure to form a blank includes: heating the composite structure to an aging temperature, and maintaining the temperature at the aging temperature for an aging time; The aging temperature is 170-200°C, or 110-150°C, or 150-180°C, or 140-180°C; The aging time is 4-10h.

Citation Information

Patent Citations

  • Electronic device and housing manufacture method thereof

    CN104219907A

  • Titanium / aluminum composite component and preparation method and application thereof

    CN107520430A